Saveriades, Alexis - (:unkn) unknown (My University, 2026)
Dr. Alexis Saveriades is a Professor with the Department of Hospitality and Tourism Management, School of Tourism Management, Hospitality and Entrepreneurship, at the Cyprus University of Technology (CUT). Professor Saveriades is the Dean School.
Keywords: Tourism Planning and Development; Tourism Policy; Strategic Planning for Tourism; Tourism Governance; business; economics; social